Environmental Sanitation in the Coastal Area of Tondonggue Village, Nambo Sub-district, Kendari City, Southeast Sulawesi Province, Indonesia - Ainani; Ferniati; Irawan Angkasa Putra (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: One of the dominant environmental health issues in Indonesia is environmental sanitation. Sanitation conditions significantly affect the overall quality of the environment. Poor environmental sanitation can result from inadequate sewage systems, substandard waste disposal facilities, unhealthy housing conditions, and toilets that do not meet health standards. Therefore, efforts to maintain and improve home sanitation should be a central focus in public health programs. Objective: This study aims to analyze the factors influencing environmental health in coastal communities in Tondonggue Village, Nambo Sub-district, Kendari City, in 2024. Methods: This research employed an analytical observational design using a cross-sectional approach to assess sanitation and environmental health conditions in the coastal area of Tondonggue Village, Nambo Sub-district, Kendari City, Southeast Sulawesi Province, Indonesia. Results: The majority of residents in Tondonggue Village demonstrated handwashing behavior that meets health standards, with a compliance rate of 84.8%. Access to clean water that meets health requirements reached 100%. Ownership of proper and self-maintained latrines also reached 100%. However, only 54.5% of household sewage disposal systems met health standards, and 60.6% of household waste disposal practices did not meet acceptable health standards. Conclusion: Environmental sanitation and health conditions in Tondonggue Village show both positive progress and critical challenges. While several indicators such as clean water access and latrine ownership are commendable, others particularly sewage and waste disposal require significant improvement. Overall, environmental sanitation in the area is relatively adequate, but targeted interventions are necessary to address the remaining deficiencies. Keywords: Sanitation, Environmental Health, Public Health, Housing Quality, Indonesia